Upaya pencegahan stunting melalui program penyuluhan pada wanita usia produktif di Dusun Guntur - Azizah, Anisatul; Pamungkas, Arya Tirta; Puspaningrum, Dyah Ayu; Ulfanny, Nadila; Ghufron, Syahrul; Hasan, Farid (Penamas: Journal of Community Service, 2024)
Efforts to prevent stunting through education programs for women of productive age are essential because there are still many cases of children affected by stunting. Prevention of stunting in Guntur hamlet, Rejosari village, Bandongan sub-district, Magelang Regency is also needed. Because stunting is a public health problem that has a long-term impact on children's growth and development, it is necessary to carry out education or counseling regarding healthy lifestyles in the community to increase knowledge and practice of healthy nutrition, good eating patterns, and health care for pregnant women and children under five. The outreach methods include educational sessions, healthy nutritional practices demonstrations, and informative materials distribution. The outreach activities received a good response from the community, and the results showed a change in understanding patterns regarding food choices, monitoring children's snacks, and concern about safe doses of MSG.